2010
DOI: 10.3324/haematol.2010.029827
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase 2 is required for chromatin condensation and subsequent enucleation of cultured mouse fetal erythroblasts

Abstract: The online version of this article has a Supplementary Appendix. BackgroundDuring the final stages of differentiation of mammalian erythroid cells, the chromatin is condensed and enucleated. We previously reported that Rac GTPases and their downstream target, mammalian homolog of Drosophila diaphanous 2 (mDia2), are required for enucleation of in vitro cultured mouse fetal liver erythroblasts. However, it is not clear how chromatin condensation is achieved and whether it is required for enucleation. Design and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(88 citation statements)
references
References 32 publications
3
84
1
Order By: Relevance
“…Our data demonstrates that normal down-regulation of Myc in late stage erythroid cells is essential for nuclear condensation and enucleation, revealing a novel role for Myc in mammalian erythropoiesis. Myc is down-regulated during the late stages of erythroid maturation, concomitant with the global histone deacetylation that is critical for erythroid nuclear condensation and enucleation (43,44). Ectopic Myc expression at physiological levels that did not induce cell cycle re-entry was sufficient to block the global histone deacetylation and inhibit nuclear condensation and enucleation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Our data demonstrates that normal down-regulation of Myc in late stage erythroid cells is essential for nuclear condensation and enucleation, revealing a novel role for Myc in mammalian erythropoiesis. Myc is down-regulated during the late stages of erythroid maturation, concomitant with the global histone deacetylation that is critical for erythroid nuclear condensation and enucleation (43,44). Ectopic Myc expression at physiological levels that did not induce cell cycle re-entry was sufficient to block the global histone deacetylation and inhibit nuclear condensation and enucleation.…”
Section: Discussionmentioning
confidence: 98%
“…Pharmacological inhibition of histone deacetylases (HDACs) has been reported to block chromatin condensation and enucleation in erythroid cells, demonstrating that global histone deacetylation observed during late stage erythroid maturation is necessary for erythroid nuclear condensation and enucleation (43,44). Recent studies have shown that Myc regulates global chromatin structure by influencing widespread histone modifications (45)(46)(47).…”
Section: Ectopic Myc Expression Inhibits Nuclear Condensation and Hismentioning
confidence: 99%
“…The study by Ji et al 10 published in this issue of the Journal provides the first detailed analyses of the expression of different HDAC isoforms during maturation of murine erythrocytes. Previous investigators had already identified that HDAC are required for chromatin condensation prior to enucleation of murine erythroblasts immortalized with the Friend virus.…”
Section: A Newly Identified Role For Histone Deacetylases In Erythropmentioning
confidence: 99%
“…APHA 9 and UBHA 24 were identified by screening a library of 24 new HDACi for their ability to reactivate g-globin expression in erythroblasts generated ex-vivo from normal donors and from β°-thalassemic patients. 16 The paper by Ji et al 10 led us to perform re-analyses for signs of enucleation in May-GrunwaldGiemsa stained smears prepared from cells obtained in the course of this previous study. Pyrenocytes (arrows) and ghosts of reticulocytes (arrow-head, reticulocytes do not survive the shear force of the centrifugation process) were easily detectable on smears of human erythroblasts induced to mature with erythropoietin for 4 days (control).…”
Section: Recent Advances In Translational Research On Histone Deacetymentioning
confidence: 99%
See 1 more Smart Citation